The Evolution Of Elucidation: The Snowden Cases Before The Investigatory Powers Tribunal. (Modern Law Review, 2022)
In 2018 the European Court of Human Rights found that the UK's Investigatory Powers Tribunal is an 'effective remedy' when it comes to reviewing the compatibility of the UK's domestic legal framework governing the interception of communication and other communications surveillance powers with the requirements of the European Convention on Human Rights. In particular, the Court praised the Tribunal's 'elucidatory function', which it performed during a series of cases that arose in the aftermath of Edward Snowden's disclosures in 2013. This article analyses and historicises the elucidatory function by comparing it with previous cases where the High Court and the IPT resolved questions of law arising from similar problems. Using insights derived from systems theory, the article argues that the elucidatory function evolved as a containment measure in response to unexpected crises of control over classified information. The procedure resolves conflicts between secrecy, security, and the publicity required by the law itself.